Simple diagnostic assay for hairy cell leukaemia by immunocytochemical detection of annexin A1 (ANXA1) - Falini, Brunangelo; Tiacci, Enrico; Liso, Arcangelo; Basso, Katia; Sabattini, Elena; Pacini, Roberta; Foa, Robin; Pulsoni, Alessandro; Favera, Riccardo Dalla; Pileri, Stefano (The Lancet (British edition), 2004)
A marker capable of distinguishing with certainty between hairy cell leukaemia and other B-cell malignant disease would be of great diagnostic value. Through gene expression profiling, annexin A1 (ANXA1) has been identified as a gene that is upregulated in hairy cell leukaemia. We did immunostaining of 500 B-cell tumours with a specific anti-ANXA1 monoclonal antibody and showed that ANXA1 protein expression is specific to hairy cell leukaemia. Immunocytochemical detection of ANXA1 represents a simple, inexpensive, highly sensitive and specific (100%) assay for diagnosis of hairy cell leukaemia. This assay will be especially useful in distinguishing hairy cell leukaemia from splenic lymphoma with villous lymphocytes and variant hairy cell leukaemia, both of which usually respond poorly to treatments that are effective in hairy cell leukaemia.